1983
DOI: 10.1002/ijc.2910310320
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity and spontaneous development of lymphoma. Effects of single and multiple injections of interferon into young and aged C57BL/6 mice

Abstract: The capacity of interferon (IFN) given once or repeatedly to augment natural killer (NK) cell activity in the spleen was tested in young and aged C57BL/6 mice. Multiple injections of 10(4) u IFN i.p. into 3-month-old or 12-month-old mice did not augment cytotoxicity mediated by NK cell activity; rather it reduced this activity in relation to the effect obtained with a single injection. When T and B cells or macrophages were removed in vitro, no restoration of NK-cell activity, and therefore no suppressor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The development of hyporesponsiveness resulting from multiple treatments with two BRMs, IFN, and MVE-2 [3,17,20,22], prompted us to test whether hyporesponsiveness would also occur with other BRMs that have been reported to augment NK-cell activity following a single treatment. Because of the possible important role of NK cells and macrophages in resistance to metastases and in BRM-mediated antitumor therapy [1,11,13,27], it was important to analyze the mechanism of hyporesponsiveness of NK activity that might be induced by BRMs and also to determine whether such hyporesponsiveness occurs with M0 activity.…”
Section: Offprint Requests To: M a Chirigosmentioning
confidence: 98%
See 2 more Smart Citations
“…The development of hyporesponsiveness resulting from multiple treatments with two BRMs, IFN, and MVE-2 [3,17,20,22], prompted us to test whether hyporesponsiveness would also occur with other BRMs that have been reported to augment NK-cell activity following a single treatment. Because of the possible important role of NK cells and macrophages in resistance to metastases and in BRM-mediated antitumor therapy [1,11,13,27], it was important to analyze the mechanism of hyporesponsiveness of NK activity that might be induced by BRMs and also to determine whether such hyporesponsiveness occurs with M0 activity.…”
Section: Offprint Requests To: M a Chirigosmentioning
confidence: 98%
“…However, recent phase-I clinical studies [17,20] and a preclinical study [3] indicate that multiple treatment with interferon (IFN) failed to boost NK activity. Similarly, while several different molecular weight maleic anhydride divinyl ethers (MVE) have been shown to significantly augment NK-cell-activity [1], we recently reported that multiple treatments with a low-molecular-weight MVE-2 led to the development of hyporesponsiveness to augmentation of NK-cell activity [22].…”
Section: Offprint Requests To: M a Chirigosmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of BRMs to augment NK activ ity in nonlymphoid organs provided a basis for investigating previous observations that the repeated administration of IFN during preclinical [67] or clinical trials [68. 69] or MVE-2 to mice [57,58,70] resulted in a hyporesponsiveness of NK activity in blood and/or in spleen.…”
Section: Augmentation Of Nk Activity In Lymphoid and Nonlymphoid Compmentioning
confidence: 99%